PROMOTIONAL STRATEGY FOR REGIONAL INVESTMENT GROWTH IN JENEPONTO REGENCY - Salam, Adnan Yahya; Arianto, Arianto; Akbar, Muh (Politeknik Negeri Ambon, 2025)
Introduction: This research investigates the investment promotion strategies carried out by the Investment and One-Stop Integrated Services Agency (DPMPTSP) of Jeneponto Regency, focusing on attracting and realizing investments in the renewable energy, tourism, and agricultural sectors. Methods: Adopting a qualitative method with a descriptive design, the study applies thematic analysis framed by two theoretical perspectives: Segmentation, Targeting, and Positioning (STP) and the Theory of Planned Behavior (TPB).Results: The findings reveal that promotional efforts include active engagement in both regional and international investment forums (such as SSIF and Dubai), the preparation of Investment Project Ready to Offer (IPRO) documents, the use of digital channels (official websites and social media platforms), and direct promotional activities through one-on-one meetings. The STP framework identifies and addresses specific investor segments with tailored messages, while TPB helps explain how attitudes, perceived social norms, and behavioral control shape investment intentions. Despite these initiatives, several obstacles remain, including budget limitations, insufficient human resource skills, weak inter-agency coordination, societal resistance, and regulatory uncertainty. Consequently, it is recommended that investment promotion strategies emphasize behavior-oriented approaches, strengthen professionalism, and enhance both regulatory and institutional frameworks. Such measures are expected to make Jeneponto’s investment promotion more effective, integrated, and sustainable in fostering regional economic growth. Keywords: investment promotion, STP (Segmentation, Targeting, Positioning), Theory of Planned Behavior, DPMPTSP, communication strategy, regional development.